2009
DOI: 10.1227/01.neu.0000327686.99072.e7
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Anterior Thoracic Spinal Cord Herniation

Abstract: Anterior thoracic spinal cord herniation is a rare cause of progressive myelopathy. Much has been speculated about the best operative treatment. However, no evidence in favor of any of the promoted techniques is available to date. Therefore, we decided to analyze treatment procedures and treatment outcomes of anterior thoracic spinal cord herniation to identify those factors that determine postoperative outcome. METHODS: An individual patient data meta-analysis was conducted, focusing on age, gender, vertebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 74 publications
1
62
0
2
Order By: Relevance
“…Increasing awareness among the treating physicians is also a contributing factor towards increased cases being reported recently. The natural history of this condition is poorly understood as there are very few cases in the literature and most of them were treated surgically [1,2]. Massicotte et al [3] reported four cases in their series that were managed expectantly in the absence of motor weakness and had no evidence of neurological deterioration at long term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Increasing awareness among the treating physicians is also a contributing factor towards increased cases being reported recently. The natural history of this condition is poorly understood as there are very few cases in the literature and most of them were treated surgically [1,2]. Massicotte et al [3] reported four cases in their series that were managed expectantly in the absence of motor weakness and had no evidence of neurological deterioration at long term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital causes implicate the possibility of a congenital dural defect/duplication of the dura with defect in the inner layer or presence of dorsal arachnoid cysts which is not infrequently associated with this condition [1,2]. Similarly, acquired etiology points it towards damage to ventral dura mater secondary to inflammation, remote spinal trauma, or thoracic disc herniation [1,2]. Irrespective of the etiology, this condition occurs only in the thoracic cord; normal kyphosis of the thoracic cord and ventral position of the midthoracic cord being implicated for the same.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations